Cu-32.02% Zn-2.30% Pb alloy surface superhydrophobicity induced by an arachidate layer - Aniedi E. Nyong; Godwin J. Udoh; Joachim J. Awaka-Ama; Joshua F. Effiong; Ifiok Ekwere; Clement Obadimu; Pradeep Rohatgi (Academia Materials Science)
A combination of thermal oxidation and chemical modification has been applied in creating a superhydrophobic surface on a Cu-32.02% Zn-2.30% Pb alloy. The thermal oxidation was initiated in air, and the chemical modification of the oxide surface was effected in 0.005 M solution of arachidic acid. Evaluation of the surfaces after the surface modification was done with SEM, XRD, FT-IR, and contact angle measurement tools. From the XRD studies, the presence of ZnO and PbO was confirmed on the oxidized surfaces. Equally from the XRD and FT-IR tools, it was confirmed that the arachidates of zinc and lead were the products formed after the chemical modification. These products existed in various nanostructural forms on the copper alloy surface. The average contact angles of water measured after the chemical modification step were 153.73 ± 7.35 and 144.94 ± 0.78 for the samples modified in 0.005 M arachidic acid for 6 and 12 hours, respectively.